IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER (PUG) DIBIDANG PENDIDIKAN DI KOTA BOGOR - Ana Sabhana Azmy; Fini Pertiwi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Gender Mainstreaming (PUG) is important to be implemented in a policy. This study aims to determine the implementation and obstacles of the Bogor mayor's regulations regarding PUG in secondary education in the city of Bogor. This is a qualitative research with case studies. Data collected by interviewing four person in education, excutive, and legislative background. Others data collected by literatur review from books and journals. The results show that the implementation of Bogor mayor's regulation No.42 of 2017 concerning General Guidelines for the Implementation of PUG in secondary education in the city of Bogor has not been maximal. The communication patterns, resources and dispositions or attitudes of the officials are not optimal to solve a gender biased as the problems. The obstacles in implementing the PUG program are; 1) PUG has only become a concern at the individual level or several work units and has not been comprehensive, 2) There are limited human resources in PUG implementing agencies in the education sector, as well as a lack of understanding of a gender- fair perspective, and 3) Communication and coordination aspects between teams are still lacking, and the absence of socialization for additional knowledge. Pengarusutamaan Gender (PUG) penting untuk diterapkan dalam sebuah kebijakan, khusus dilingkungan pendidikan. Penelitian ini bertujuan untuk mengetahui implementasi serta hambatan dari peraturan walikota Bogor terkait PUG pada lingkup pendidikan menengah di kota Bogor. Penelitian ini merupakan penelitian kualitatif dengan studi kasus. Data penelitian dikumpulkan dengan mewawancarai empat informan dibidang pendidikan, eksekutif, dan legislatif. Data lain diperoleh dari studi literatur, baik buku ataupun jurnal dan dokumen pendukung lainnya. Hasil penelitian menunjukkan bahwa implementasi peraturan walikota Bogor No.42 tahun 2017 tentang Pedoman Umum Pelaksanaan PUG pada pendidikan menengah di kota Bogor belum maksimal. Pola komunikasi, sumber daya dan disposisi atau sikap aparat belum maksimal dan bertanggung jawab terhadap kebutuhan dan masalah pemahaman yang bias gender. Hambatan dalam implementasi program PUG dibidang Pendidikan tersebut adalah; 1) PUG baru menjadi kepedulian ditingkat individu atau beberapa unit kerja dan belum menyeluruh, 2) Adanya keterbatasan SDM di instansi penyelenggara PUG bidang pendidikan, serta kurangnya pemahaman akan perspektif adil gender, dan 3) Aspek komunikasi dan koordinasi antar tim masih kurang, serta ketiadaan sosialisasi untuk penambahan pengetahuan.